IMPLEMENTATION OF SHORT TERM PRISON CRIMINALS AGAINST CHILDREN IN MARTAPURA CLASS 1 SPECIAL CHILD DEVELOPMENT INSTITUTIONS - Napitupulu, Surya Pandapotan (Universitas Muhammadiyah Tapanuli Selatan, 2024)
The aim of this research is to analyze the implementation of short-term imprisonment for children in special children's development institutions and whether legal justice has been provided. The method used is an empirical legal research type using interview techniques and questionnaires carried out at the Martapura Class I Special Children's Development Institution as a result of this research is Punishment of children is carried out in an educational criminal law system, meaning that the programs given to children serving prison sentences in correctional institutions or development institutions must aim at an educational element. The essence of child protection is in conflict with the law to ensure that children's rights are still provided. even though they are experiencing the problem of a second criminal act. When imposing criminal sentences on children, including imprisonment, children's rights must be taken into account, so the protection of children can be realized in the criteria for imposing warning sentences. In applying diversion to children who are in conflict with the law, diversion is applied to all criminal acts committed by children without having to differentiate between the threat of non-criminal punishment and repetition of criminal acts. The difference in treatment in giving punishment to the child will have an impact on the child's future. Children who come out of prison will be labeled as bad children and of course this has a psychological impact on children. Application of restorative justice (restorative justice) cannot yet be carried out in full because the SPPA Law provides limits on criminal acts that can be committed for diversion.